Sn-induced CuO–CeO2 catalysts with improved performance for CO preferential oxidation in H2-rich streams. (23rd June 2021) - Zhang, Zhijun; Chen, Kezhen; Lu, Jichang; Zou, Qin; Zhao, Yuhui; Luo, Yongming; He, Dedong; Li, Rongtao
Abstract: Sn modified CuO–CeO2 catalysts with different Sn loadings were prepared by a facile, green and solvent-free method. The effect of Sn/Ce ratio over Sn–Cu–Ce-x (x = 0, 1, 2.5, 5, 7.5) samples on CO activity and O2 selectivity was investigated. The samples were characterized by various techniques using N2 -adsorption/desorption, XRD, H2 -TPR, XPS, Raman and in-situ DRIFTS. It was revealed that stronger interaction between acitve sites and support, higher amounts of Sn 2+ and Ce 3+, associated with increased amount of oxygen vacancies, were observed on the catalyst of Sn–Cu–Ce-5. As a result, the optimized catalyst displayed an excellent catalytic performance even in the presence of CO2 and H2 O. In this sense, probing the Sn modified CuO–CeO2 catalyst can elucidate some useful keys for the development of high CO2 and H2 O-resistance catalyst during CO-preferential oxidation in H2 -rich streams. Graphical abstract: Image 1 Highlights: Sn-induced CuO–CeO2 catalysts was prepared for CO-PROX. Modifying by Sn improved low-temperature catalytic performance. The enhanced activity was due to the formation of Sn–Cu–Ce–O solid solution. Sn–Cu–Ce displayed good stability within 360 h in presence of CO2 and H2 O.